Occurrence of Mycoplasma gallisepticum and avian metapneumovirus in commercial broiler flocks from the Southeast and Midwest regions of Brazil - Secato, Caroline Tostes [UNESP]; Montassier, Maria De Fátima Silva [UNESP]; Fernando, Filipe Santos [UNESP]; Lopes, Priscila Diniz [UNESP]; Pavani, Caren [UNESP]; Montassier, Helio José [UNESP] (Instituto Biológico, 2024)
Respiratory tract infections in poultry have become serious problems with negative consequences for poultry production. Among these diseases, mycoplasmosis and avian pneumoviruses stand out, which, despite being relevant in poultry health, have not been systematically investigated in Brazil, especially regarding the interaction between these agents or the occurrence of co-infection in broiler chickens. The present study investigated the occurrence of infection by Mycoplasma gallisepticum (MG) and subtypes A and B of avian metapneumovirus (aMPV) in broiler chickens from commercial poultry flocks kept on farms with high biosecurity standards and located in the Southeast and Midwest regions of Brazil. Polymerase chain reaction (PCR) and reverse transcription nested-PCR techniques were applied to detect and/or identify, respectively, MG and aMPV in samples of nasal and tracheal swabs collected between 2017 and 2018, from 87 batches of broiler chickens from 15 commercial production farms that showed respiratory clinical signs. Two out of 87 batches sampled (2.3%) were positive for MG, while none of them were positive for aMPV. The low or no incidence of these pathogens can be explained by the adoption of increasingly effective health control measures for these agents on farms with high biosecurity standards. In addition, there are clues that other bacterial and viral infectious agents may be involved in the etiology of respiratory problems of these broiler chickens, which showed clinical signs of respiratory diseases upon sample collection.
Keywords: broiler production; PCR; respiratory diseases; RT-Nested-PCR